Evaluation of compressive strength of cement-stabilized rammed earth wall by ultrasonic-rebound combined method. (1st June 2023) - Zhou, Tiegang; Zhang, Huiyuan; Li, Boyang; Zhang, Liangyi; Tan, Wei
Abstract: It is difficult to guarantee the construction quality of rammed earth buildings, and there needs to be more guidance for the quality inspection of historical protection buildings. To facilitate the assessment of the quality of rammed earth walls, based on the establishment of concrete strength measurement curves, this study took the additive content and type with curing time as variables, and considered the rebound (R) values and ultrasonic pulse velocity (UPV) values in the dense and sparse zones. Based on the material strength theory, the strength measurement curve of cement-stabilized rammed earth was finally established in the sparse zone. The single-factor method and two-factor method were considered to evaluate the unconfined compressive strength (UCS), respectively. The results showed that the R value and UPV increased with the increase in cement content. With the increase in curing time, the R value increased and stabilized; the UPV increased, decreased, and finally stabilized. The difference in the R value of the sparse and dense zones is within ±1, and the difference in the UPV is within ±0.2 km/s. The single R method or UPV method predicts the UCS with poor accuracy, while the ultrasonic-rebound combined method can better predict the UCS. Finally, samples from the failed specimens were taken for scanning electron microscopy tests to further verify the test results on a microscopic level. Highlights: The variation of UPV and R value with curing time of cement-stabilized rammed earth was investigated. The difference in the R values of the dense and loose zones is within 1, and the difference in the UPV is within 0.2 km/s. At the same curing time, the cement content has a greater effect on the R value and UCS compared to the moisture content. The ultrasonic-rebound combined method can better predict the UCS of rammed earth.